Respuesta :
just so u know, ur output value is f(x) and ur input value is x
f(x) = -2x^2 - 3x + 5....when ur input value(x) is -3
f(-3) = -2(-3^2) - 3(-3) + 5 =
f(-3) = -2(9) + 9 + 5
f(-3) = -18 + 14
f(-3) = -4 <==
f(x) = -2x^2 - 3x + 5....when ur input value(x) is -3
f(-3) = -2(-3^2) - 3(-3) + 5 =
f(-3) = -2(9) + 9 + 5
f(-3) = -18 + 14
f(-3) = -4 <==
By evaluating the function in x = -3, we will see that:
f(-3) = -4
How to evaluate a function?
Evaluating a function in a given number means that we just need to replace the variable by the given number.
Here we want to evaluate:
f(x) = -2*x^2 - 3*x + 5
in x = -3
We will get:
f(-3) = -2*(-3)^2 - 3*(-3) + 5
= -2*9 + 9 + 5 = -18 + 9 + 5 = -4
Then we have:
f(-3) = -4
If you want to learn more about evaluating functions, you can read:
https://brainly.com/question/4344214